2021
DOI: 10.1186/s12944-021-01496-8
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic index of plasma is related to coronary atherosclerotic disease in elderly individuals: a cross-sectional study

Abstract: Background Dyslipidaemia plays an important role in coronary atherosclerotic disease (CAD). The relationship between the atherogenic index of plasma (AIP) and CAD in elderly individuals was explored in this study. Methods Elderly individuals (age ≥ 65 years) who underwent coronary angiography from January 2016 to October 2020 were consecutively enrolled in the study. Results A total of 1313 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“… 20 In previous study, AIP was positively related to the severity of CAD in elderly individuals and was superior to other lipid profiles. 21 So we compared the differences between AIP and TyG for coronary artery disease in postmenopausal women.In addition, Wang et al demonstrated that the AIP, as a biomarker, assists in the prevention of CAD in the Chinese population. 12 Guo et al and Wu et al observed that AIP could be a powerful independent predictor of CAD risk in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“… 20 In previous study, AIP was positively related to the severity of CAD in elderly individuals and was superior to other lipid profiles. 21 So we compared the differences between AIP and TyG for coronary artery disease in postmenopausal women.In addition, Wang et al demonstrated that the AIP, as a biomarker, assists in the prevention of CAD in the Chinese population. 12 Guo et al and Wu et al observed that AIP could be a powerful independent predictor of CAD risk in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Atherogenic index (AI), when elevated, is a marker of early atherosclerosis [119], [120]. Patients with IS may suffer from intracranial atherosclerosis that worsens IS severity and outcomes [121], [122].…”
Section: ) Biochemical Markers Of Unfavourable Stroke Outcomesmentioning
confidence: 99%
“…SdLDL-C has been listed as a potential biomarker of cardiovascular disease [ 23 ]. Studies have found that AIP is a novel marker of cardiovascular disease [ 24 , 25 ] and may be superior to traditional lipid parameters [ 26 28 ]. Nevertheless, only a few studies have been conducted regarding the association between AIP and intracranial or extracranial atherosclerotic stenosis; the predictive value remains unclear for intracranial atherosclerotic stenosis [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%